Jenis dan Sebaran Uca spp. (Crustacea: Decapoda: Ocypodidae) di Daerah Mangrove Delta Mahakam, Kalimantan Timur - Rianta Pratiwi (Jurnal Perikanan Universitas Gadjah Mada, 2007)
Studies on the species and distribution of Uca spp. in mangrove area of Mahakam Delta, East Kalimantan was conducted in July 2004. The aims of this study were to know distribution and characteristics of Uca spp. as permanent and dominant species in the mangrove area. Sampling method used in this study was quadrat transect. Results indicated that the highest density of species was Uca (Deltuca) dussumieri dussumieri with density of 912 and 656 individu/m² in Muara Bayor and Muara Beji, respectively. Uca (Australuca) bellator minima and Uca (Deltuca) arcuata both in Muara Bayor had the lowest density at 11 and 12 individu/m², respectively. Those crabs were clump distributed in their live.